Risks Analysis Of Carbon Dioxide Storage In Geological Formations - Lusyana Lusyana; M Dwi Atmanto (Scientific Contributions Oil and Gas, 2011)
Concerning to global climate change, Indonesia has committed to reduce CO2 emissions. The CO2 injection and storage in underground geologic formations is one practical method for reducing large volumes of CO2 emissions into the atmosphere. However, the risks associated with the geological storage of CO2 are a key factor affecting the implementation of Carbon Capture and Storage (CCS). A better understanding and quantification of these risks is required to ensure risks associated with CO2 storage in underground formations meets acceptable safety standards. In this paper, the risks are quantified and justified by using Subjective Risk Assessment method. The results show that the risks are low through medium for three types of geological formations i.e. depleted oil and gas reservoirs, unmineable coal seams, and deep saline reservoirs.